Islamic Microfinance Institutions, Indonesian Economic Democracy, and Development (A Maqashid Approach System Perspective) - Ihsan Rois; Muh. Salahuddin (Jurnal Iqtisaduna, 2022)
This study aims to expand on the theoretical notions of sharia economics, economic democracy, and Indonesian development. Economic identity is influenced by religion, culture, and other valuable components of life, including the state's ideology. Religious ideals, cultural constructions, governmental ideology, and/or a synthesis of these values should all be protected from development. This is Auda's considerable offer, which connects maqasid al-shariah with systems theory to bolster Islamic studies' intellectual integrity. The Shariah economy, social system, and state ideology should be united to attain economic welfare. As a result, the maqashid shariah system approach provides a methodological framework for examining the existence of shariah microfinance institutions, economic democracy, and development in their entirety